The influence of sufism on the development of Persian mosque architecture / Ali Goodarzi - Goodarzi, Ali (2014)
Mosques have always been recognized along with a series of patterns (archetypes) such as the dome, the arch, the mihrab, the courtyard, the portal and the minaret, which have shaped the architecture language of the Islamic place of worship worldwide. However these set of patterns did not exist in the creation of the first mosques, and in the third and fourth century A.H. emerged and developed gradually as major features of the mosque in the Persian lands and provided definitive functions in the congregational Muslim rituals. At the time of these constructive changes in the body of the mosque in Persia an ideological shift also developed from traditional Islam, towards a more esoteric experience known as Sufism. The Author believes that the Sufism movement has had a significant role in the development occurred in the Persian mosque architecture and the introduction of the 6 main patterns. However no research has directly addressed the connection between Sufism and these changes. Thus the aim of this research is to examine whether or not the Sufi ideology has been the main reason that has led to the introduction of the 6 main patterns of the Persian mosque, and to explore the physical, emotional, mental and spiritual influences of the Sufi ideology on the 6 main patterns of the Persian Mosque; and whether they have helped in creating a better ambiance for the act of worship. The research deploys two case studies on the Grand Mosque and Imperial Mosque of Esfahan, based on a qualitative approach. The results of a thorough study on the Sufi ideology, in-depth structured interviews and a deep direct observation on the 2 cases mentioned, prove the influence of Sufism in the creation of the 6 patterns of mosque architecture in Persia. The results further reveal how these 6 patterns have contributed to providing a better ambiance in the mosque for the act of worship by creating a unique spiritual experience for the worshippers.